Perceived Environmental Factors And The Intention To Adopt A Standard Business Reporting Facility: A Survey Of Australian Corporate Cfos - Saiful Azam, Saiful Azam (Asian Academy of Management (AAM), 2014)
The Australian government's extensible business reporting language (XBRL)-derived reporting facility, called Standard Business Reporting (SBR), went 'live' to companies in 2010. Its voluntary take-up by companies has been poor following a promotion that emphasised its technological benefits. This study seeks to identify a set of perceived environmental factors and examine how these factors influence managerial intention to adopt SBR. A survey instrument is developed to measure the extent of the competitive pressure, government pressure and external communication perceived by the Chief Financial Officers (CFOs) of listed companies as influences on their firms' intention to adopt SBR. Based on 54 usable responses by CFOs of relatively large listed companies, the survey results reveal that, contrary to the expectation, no significant association exists between perceived competitiveness in the industry and the intention to adopt SBR. However, CFOs regard becoming a leader or an early follower as a significant consideration influencing their firms' intentions to adopt SBR. As the paper reports, CFOs believe that they do not have adequate information about SBR from external sources. Communication about SBR is found to be significantly related to the intention to adopt SBR. Interestingly, government pressure is not found to relate to the intention to adopt SBR. Implications of these environmental influences for the successful voluntary take-up of SBR in Australia are discussed.